Ultra‐Low Frequency Waves in the Hermean Magnetosphere: On the Role of the Morphology of the Magnetic Field and the Foreshock. Issue 24 (26th December 2022) - Kallio, E.; Jarvinen, R.; Massetti, S.; Alberti, T.; Milillo, A.; Orsini, S.; De Angelis, E.; Laky, G.; Slavin, J.; Raines, J. M.; Pulkkinen, T. I.
Abstract: Ultra‐low frequency (ULF) waves have been observed in the Mercury's magnetosphere by the Mariner 10 and MErcury Surface, Space ENvironment, GEochemistry and Ranging missions. The observed ∼2 s (∼0.6 Hz) period waves in the magnetic field are proposed to be generated by dynamic processes in the Mercury's magnetosphere. We investigate the Hermean ULF waves with a global hybrid model. We found evidence for ∼2‐s circularly polarized right‐handed waves in Mercury's magnetosphere at the closest approach of BepiColombo mission's first Mercury flyby in the model. The most intense wave power occurs on the dawn side closed magnetic field lines. These waves were found to be generated on the hemisphere which is magnetically directly connected to the interplanetary magnetic field on the dayside and to the foreshock region. It is therefore possible that the generation mechanism of these waves is associated with the precipitating ion flux or with the wave activity in the foreshock region. Plain Language Summary: Mercury's space environment includes several types of waves. Many of them are associated with the magnetosphere, which is the region dominated by the planet's intrinsic magnetic field and the solar wind. Low frequency waves at about 2‐s period were measured in the magnetic field by Mariner 10 and MErcury Surface, Space ENvironment, GEochemistry and Ranging spacecraft near the planet. The origin of these waves is proposed to be dynamical processes in the Mercury‐solar wind interaction. Here we investigate the 2‐s waves with a large‐scale computer simulation model, which covers global three‐dimensional space and resolves detailed solar wind ion movement and electromagnetic fields in the solar wind and magnetosphere around Mercury. Our analysis suggests that these waves occurred at the closest approach of BepiColombo mission's first Mercury flyby on 1 October 2021, in the dawn side of Mercury's magnetosphere. This location is connected via magnetic field lines to the solar wind in the day side of the planet. The waves may be generated in the solar wind before it encounters the Hermean magnetosphere or may be associated with ions traveling toward the planet's surface. Key Points: Ultra‐low frequency waves in Mercury's magnetosphere were investigated with a global hybrid model About 2‐s period circularly polarized right‐handed waves occur on closed field lines along BepiColombo's first Mercury flyby in the model The waves are generated on the hemisphere which is directly magnetically connected to the interplanetary magnetic field and to the foreshock